2021
DOI: 10.1002/adfm.202009994
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in 2D‐Nanomaterial‐Based Triboelectric Nanogenerators

Abstract: The integration of triboelectric nanogenerators (TENGs) and 2D nanomaterials brings about 2D‐nanomaterial‐based TENGs (2D‐TENGs) that promote the rapid development of self‐powered sensing systems and wearable electronics. Extraordinary physical, electronic, chemical, and optical properties of 2D nanomaterials endow 2D‐TENGs with improved output performance. This review presents the state of the art of 2D‐TENGs with respect to basic classifications, enhancement mechanisms, special advantages, output performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 85 publications
(104 reference statements)
1
68
0
Order By: Relevance
“…Previous investigations have outlined the power density output from piezoelectric nanogenerators 66 and triboelectric nanogenerators 67 to be within the range of 4.41 to 5.92 μWcm −2 and 400 to 50,000 μWcm −2 , respectively. The predicted InN bilayer nanogenerator shows a decent maximum power density and a considerable induced electrical output voltage, which is comparable to the theoretically and experimentally addressed triboelectric nanogenerators of Janus TMD bilayers 17 , GaN nanowire array 68 , h -BN polypropylene 69 , monolayer MoS 2 flake 70 , and bilayer PVDF-TrFE and graphene oxide 66 , as outlined in Table 1 .…”
Section: Resultssupporting
confidence: 74%
“…Previous investigations have outlined the power density output from piezoelectric nanogenerators 66 and triboelectric nanogenerators 67 to be within the range of 4.41 to 5.92 μWcm −2 and 400 to 50,000 μWcm −2 , respectively. The predicted InN bilayer nanogenerator shows a decent maximum power density and a considerable induced electrical output voltage, which is comparable to the theoretically and experimentally addressed triboelectric nanogenerators of Janus TMD bilayers 17 , GaN nanowire array 68 , h -BN polypropylene 69 , monolayer MoS 2 flake 70 , and bilayer PVDF-TrFE and graphene oxide 66 , as outlined in Table 1 .…”
Section: Resultssupporting
confidence: 74%
“…Embedding a superior intermediate layer into TENGs was also proved as an efficient strategy to enhance the surface charge density and power output performance that are attributed to the enhancement of the dielectric permittivity [6,51,123]. The research shows that the triboelectric charge in the friction dielectric layer will decay with time.…”
Section: Intermediate Layer Embeddingmentioning
confidence: 99%
“…MXenes are electronegative materials owing to their electric negative surface groups such as −OH and −F, making them candidate triboelectric materials for use in TENGs. 95 Reports have indicated that MXenes can be more negative than PTFE. 96 …”
Section: Inorganic Nanomaterials Used In Tengsmentioning
confidence: 99%